Kinetics and Mechanism of Ru(VIII)-Catalysed Oxidation of Methyl Glycol by Ce(VI) in Perchloric Acid Medium - Bhushan Singh, Shashi; Singh, Darshana; Prakash Sahay, Ved; Prasad, Manju; Prasad, Janak (Asian Journal of Chemistry, 2010)
The kinetics of ruthenium(VIII) catalysed oxidation of methyl glycol by ceric perchlorate in perchloric acid medium have been studied. The reaction exhibits zero-order kinetics in Ce(IV) and first order rate dependence with respect to each of methyl glycol and Ru(VIII). Negligible effect of [H+] and ionic strength of the medium has been observed. A suitable mechanism, consistent with the observed kinetic data, is proposed.